EXPLORING EFL STUDENTS’ SKIMMING EXPERIENCESTHROUGH METACOGNITIVE STRATEGIES IN DIGITAL E-BOOK READING - Gadis Pujawiyanti; Rizky Sangaji (JEIT (Journal of Educational Innovations and Technologies), 2026)
This study aims to examine the use of metacognitive-based skimming strategies in the context of academic reading through e-books in EFL students. This study uses mixed method design with sequential explanatory approach to integrate quantitative and qualitative data systematically. The study participants consisted of ten students of the fifth semester of the English Language Education Study Program at Universitas Kuningan who were selected through convenience sampling and involved in all stages of the research. Data collection was conducted through four stages, namely initial observation to identify student skimming strategies before intervention, application of metacognitive-based skimming learning that includes planning, monitoring, and evaluation stages, filling out questionnaires through Google Forms, and open interviews to explore student experiences and reflections. Quantitative Data were analyzed using descriptive statistics, while qualitative data were analyzed thematically. The results showed that in the early stages, most students apply skimming intuitively and unstructured with a limited level of metacognitive awareness. After the implementation of metacognitive-based learning, students showed a significant improvement in setting reading goals, controlling the skimming process, as well as evaluating the accuracy of the main ideas obtained.